Sistem Informasi Perpustakaan Berbasis website - alfiah, nurul; Indriani, Hellena (STMIK Komputama Majenang, 2021)
School libraries must be built and developed properly in order to provide a service to students, library admins, and leaders in finding a book reference. This information service can also be done well and can be seen in the ease of members to get accurate and fast information, so from changing the form of data processing that is still manual to computer-based data processing is one of the innovations to overcome delays in information and difficulty processing detailed data collection of existing books. The Diponegoro Majenang Middle School library is still using the manual method, there is no website or application program that can process class data, member data, loan and return transactions, loan transaction reports, returns and late returns. is due on the due date for returning to the library. The method used in making this website-based library information system is the waterfall method which consists of several stages, namely Analysis, Design, Coding, Testing and Maintenance. With the development of data communication technology, school library information systems can be built as a means of online library information systems (website-based).